Características de carcaça e qualidade da carne de vacas de descarte Nelore e cruzadas - Karla Izidio Latta (2022)
Among the determining factors in beef quality, genetics is an important strategy, and greater meat quality has been observed for taurine animals over zebu. Crossbreeding has been used to enable the use of taurine genetics in tropical conditions, generating animals that add meat quality and adaptation. In the literature, there are studies that attest that this strategy is interesting, however, they are restricted to animals slaughtered up to three years of age, with no results being found for crossbred cull cows. Therefore, one hypothesis for improving the quality of the final product would be that the genetic group has an influence on the meat and carcass quality of beef cows destined for slaughter, making it possible to add value to the meat produced by crossbred cows. Thus, the objective of this study was to evaluate Nelore, ½ Angus + ½ Nelore and ½ Caracu + ½ Nelore cows as to their meat and carcass quality. For this purpose, 48 cows being 16 Nelore, 16 ½ Angus + ½ Nelore and 16 ½ Caracu + ½ Nelore, were slaughtered at the end of eight gestation seasons, with approximately 11 years of age. Carcass analyses were performed, evaluating slaughter weigth (PCabate), hot carcass weight (PCQ), carcass yield (RC), backfat thickness (ACAB), fat distribution (DIST), carcass conformation (CONF), marbling visual score (MAR), subcutaneous fat thickness (EGS), rib eye area (AOL), internal (PROFINT) end chest depth (PROFEXT), carcass length (COMP), physiological maturity (MAT), muscle color (COR) and texture (TEXT). For the meat analysis the samples taken from the Longissimus dorsi muscle were analyzed after zero and 14 days of maturation for losses by swelling, cooking losses, pH of zero and 14 days of maturation meat, light components (L*, a* and b* 0 and 14 days) and shear force (FC 0 and 14 days). NEL and ANGNEL cows showed higher EGS values when compared to CARNEL breeds. For the characteristics of AOL, PROFINT and PROFEXT, ANGNEL and CARNEL breeds obtained higher results when compared to NEL. When evaluating the COMP, ANGNEL breeds obtained greater measurements when compared to NEL, and CARNEL had intermediate values. There was no significant difference for the variables RC, ACAB, DISTR, CONF, MARM, MAT, COR and TEXT. A significant difference was observed only for the characteristic L* (0 and 14 days of maturation), in which NEL cows presented darker meat than ANGNEL cows, with CARNEL cows presenting intermediate results. There was no significant difference between the three groups of cows for the other evaluated characteristics. The ether extract (EE) of the samples was also evaluated according to the genetic group of the cows. Then it was concluded that ½ Angus + ½ Nelore cows produced better quality carcasses when compared to meat from Nelore and ½ Caracu + ½ Nelore cows and that the meat quality of Nelore and crossbred cows is similar.